2018
DOI: 10.1080/14767058.2018.1484089
|View full text |Cite
|
Sign up to set email alerts
|

ELABELA plasma concentrations are increased in women with late-onset preeclampsia

Abstract: ELABELA plasma concentrations are higher in patients with late-onset preeclampsia than in those with a normal pregnancy. However, women with early-onset preeclampsia have similar ELABELA plasma concentrations to those with a normal pregnancy. These findings provide insight into the ELABELA axis during the human syndrome of preeclampsia. In addition, these data support the concept that different pathophysiologic mechanisms are implicated in early- and late-onset preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 151 publications
(164 reference statements)
1
36
1
Order By: Relevance
“…However, we question whether the custom-made enzymelinked immunosorbent assay (ELISA) accurately measured ELA in murine maternal blood. Of note, using the same ELISA kit, both the Pritchard et al 2 and Panaitescu et al 3 studies found different ELA concentrations in samples collected at term (w30 pg/ml and 5 ng/ml, respectively, corresponding to a ratio of approximately 5000). Using a different ELISA, our results are similar in range to those from Panaitescu et al (w10 ng/mL).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, we question whether the custom-made enzymelinked immunosorbent assay (ELISA) accurately measured ELA in murine maternal blood. Of note, using the same ELISA kit, both the Pritchard et al 2 and Panaitescu et al 3 studies found different ELA concentrations in samples collected at term (w30 pg/ml and 5 ng/ml, respectively, corresponding to a ratio of approximately 5000). Using a different ELISA, our results are similar in range to those from Panaitescu et al (w10 ng/mL).…”
Section: Discussionmentioning
confidence: 92%
“…1 However, the level of current evidence linking the human maternal preeclamptic phenotype to maternal blood soluble form of VEGF-R1 (sflt1) increase is so high, and the hypoxic RNA signal in ELA-deficient placentas so strong, that the lack of sFlt1 increase, at the protein level, in the murine model is puzzling. Two human studies subsequently found no ELA decrease in maternal blood, either at delivery in women with preterm PE (mean gestational ages, 29.4 and 30.8 weeks), 2,3 or in late-onset PE (mean gestational age, 37.6 weeks), whereas ELA was actually increased. 3 Given these contradictory findings and the claim that ELA acts independently and earlier than sFlt1, 1 we investigated whether ELA was dysregulated before PE onset.…”
Section: Objectivementioning
confidence: 98%
See 1 more Smart Citation
“…reported that ELABELA plasma levels are higher in patients with late-onset preeclampsia compared to gestational-age-matched controls with a normal pregnancy or women with early-onset preeclampsia. 11 These results contrast the finding by Ho et al that suggests the deficiency of ELABELA causes preeclampsia. 5 Comparing and contrasting these results provide insight into the ELABELA axis during human pregnancy.…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, knockdown of LIN28B (an RNA‐binding protein that influences stem cell maintenance and metabolism) suppresses Elabela expression and Elabela deficiency is a promoter of preeclampsia and cardiovascular defects (including in angiogenesis) in mice . This experimental link has to be further investigated, since two recent clinical studies did not confirm the lack of Elabela in the blood and placenta of women with early and late preeclampsia . This topic is a still emerging and relevant one with regard to both pathophysiological events and the potential function of the apelinergic system.…”
Section: Emerging Potential Of the Apelinergic System For Treating Prmentioning
confidence: 99%